Assessing Water Pollution at Sail River: Insights from Plankton Abundance as an Ecological Indicator in Riau, Indonesia - Marta Dinata; Rahmat Ramadansur; Al Khudri Sembiring; Irwan Effendi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Plankton is an effective bioindicator for diagnosing freshwater pollution. We assessed the plankton community structure at three Sail River sites representing residential, industrial-urban, and agro-rural influences, and correlated biological indices with physicochemical parameters. Purposeful sampling and standard microscopy were used to identify and quantify taxa; Shannon diversity (H′), equitability index (E), dominance (D), trophic status, and saprobicity were obtained. In total, 106 taxa were recorded (zooplankton: 4 species in 3 higher groups; phytoplankton: 102 species in 20 classes). Phytoplankton abundance ranged from 3.0–9.1 × 10³ cells L⁻¹ across sites (mesotrophic), while zooplankton ranged from 1.9–161 × 10³ individuals L⁻¹. Phytoplankton diversity was moderate to high (H′ = 2.1–3.2) at less impacted sites and lower at residential sites; zooplankton diversity was low to moderate (H′ = 1.3–1.5). Saprobicity scores indicated β–α mesosaprobic conditions (light to moderate organic impact), consistent with elevated COD and low DO at residential sites. Cyanophyceae and Euglenophyceae were more frequent at sites with higher organic and nutrient loads, while Bacillariophyceae increased with increasing water clarity/flow. Overall, plankton metrics and chemistry indicated local organic stress rather than an “unpolluted” state. We emphasize the need for seasonal replication and more accurate quantification to reduce uncertainty in abundance estimates.